2015
DOI: 10.1016/j.atherosclerosis.2015.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Alpha1beta1 and integrin-linked kinase interact and modulate angiotensin II effects in vascular smooth muscle cells

Abstract: The effects of angiotensin II (Ang II) on vascular smooth muscle cells (VSMC) are modulated by reactive oxygen species (ROS) and also involve integrin engagement. However, the potential link between alpha1beta1 integrin signaling with NOX system and their combined contribution to Ang II effects on VSMC have not been investigated. We aimed to elucidate the moslecular mechanisms underlying the activation of these two pathways in Ang II effects on VSMC. Ang II-induced VSMC migration (2-fold increase) and prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 39 publications
(68 reference statements)
4
33
0
1
Order By: Relevance
“…However, integrin signaling may also contribute to vasoconstriction, as treatment with the integrin inhibitor RGDS reduced vasoconstriction to AngII but not other vasoconstrictors [198]. While α1β1 has largely been implicated in maintaining the contractile phenotype in atherosclerosis, smooth muscle hypertrophy to chronic AngII stimulation is reduced in α1 knockout mice [199], and inhibiting α1β1 using siRNA knockdown or peptide inhibitors blunts AngII-induced ERK activation and proliferation [195, 200]. Consistent with this association, AngII promotes α1 integrin expression [199] along with the expression of multiple provisional matrix-binding integrins, such as α8, β1, and β3 [201, 202].…”
Section: Integrins In Smooth Muscle Migration and Proliferationmentioning
confidence: 99%
“…However, integrin signaling may also contribute to vasoconstriction, as treatment with the integrin inhibitor RGDS reduced vasoconstriction to AngII but not other vasoconstrictors [198]. While α1β1 has largely been implicated in maintaining the contractile phenotype in atherosclerosis, smooth muscle hypertrophy to chronic AngII stimulation is reduced in α1 knockout mice [199], and inhibiting α1β1 using siRNA knockdown or peptide inhibitors blunts AngII-induced ERK activation and proliferation [195, 200]. Consistent with this association, AngII promotes α1 integrin expression [199] along with the expression of multiple provisional matrix-binding integrins, such as α8, β1, and β3 [201, 202].…”
Section: Integrins In Smooth Muscle Migration and Proliferationmentioning
confidence: 99%
“…In addition, they also exhibit uniquely exclusive effects on smooth muscle cells [191,192], fibroblast-like cells [193,194], chondrocytes [195], osteoblasts [196], and neuronal progenitors [197]. Recent studies using obtustatin has shown that α 1 β 1 integrin and integrin-linked kinase modulate angiotensin II effects in vascular smooth muscle cells and thus, are potential targets to the development of more effective therapeutic interventions in cardiovascular diseases [198,199]. Thus, D and C domains selectively target specific integrins and play critical role in our understanding of cell biology.…”
Section: Svmps As Research Tools and Diagnostic And Therapeutic mentioning
confidence: 99%
“…Periodic mechanical stress enhances ILK activity ILK is widely considered to be an intracellular adaptor that couples integrins modulating multiple cellular responses (Bhattacharya et al, 2015;Moraes et al, 2015). Hsu et al (2007) reported that ultrasound stimulation significantly enhanced the catalytic activity of ILK, leading to increased COX-2 expression in chondrocytes.…”
Section: Resultsmentioning
confidence: 99%